Testing Some Predictions of Human Capital Theory: New Training Evidence from Britain - Booth, Alison L.; Bryan, Mark L. (The Review of Economics and Statistics, 2005)
We confront the predictions of various theories with new training data from the British Household Panel Survey. We find that employer-financed training is associated with significantly higher wages at current and future firms, with a larger impact in future firms. This is consistent with human capital theory with credit constraints and with the new training literature assuming imperfectly competitive labor markets.